Study on Consumers Preference and Acceptability of Meat Pies Made From Beef and Broiler Chicken Meat - Sanusi, A. Z.; Nasir, S.; Salisu, U. S.; Suleiman, A.; Saidu, S. S.; Talabi, A. E.; Okache, T. A.; Yahaya, A. (Sahel Journal of Life Sciences FUDMA, 2025)
The study was carried out to evaluate consumers' preference, acceptability, and sensory attributes of pies made using beef and broiler chicken meat at the Animal Product and Processing Laboratory of the Department of Animal Science, Federal University Dutsin-Ma. Sixteen (16) trained panelists were used to examine the sensory attributes, preference and acceptability of the pies using a five-point hedonic scale. Data obtained on saltines, appealness, flavourness, aroma, tenderness, juiciness, and overall preference/acceptance were analysed using a general linear model of the SPSS version 2016. The results show that 26% of the respondents perfectly accepted the pie made using beef while only 23% of the respondents perfectly accepted the pie made from broiler chicken. There were no significant differences (p<0.05) in preference and sensory attributes of pies made from both meat sources. It is concluded that beef pie had more acceptability than broiler chicken pie.